2012
DOI: 10.1007/s00417-012-2241-z
|View full text |Cite
|
Sign up to set email alerts
|

Photophobia measurement in intermittent exotropia using the contrast sensitivity test

Abstract: The mesopic contrast sensitivity with glare can represent the photophobia of children with X(T). Contrast sensitivity may be a useful measure for monitoring symptoms related to X(T).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
3
11
2
1
Order By: Relevance
“…This differed from the results of Chung et al [ 7 ], who suggested that the CS was significantly reduced by glare stimulation at intermediate spatial frequency under mesopic conditions, which could possibly be due to differences in spatial frequencies according to the devices used to conduct the CS test. While Chung et al [ 7 ] performed the CS test using the Optec 6 500 vision testing system based on spatial frequencies of 1.5, 3, 6, 12, and 18 cpd, our study was conducted under visual angles of 6.3°, 4°, 2.5°, 1.6°, 1°, and 0.64° (1.1, 1.8, 2.9, 4.5, 7.1, and 10.2 cpd, respectively). This difference may have introduced a lower spatial frequency bias in the test results, which is equal to larger visual angles in our study, and lowered the difference between CS caused by glare stimulation.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This differed from the results of Chung et al [ 7 ], who suggested that the CS was significantly reduced by glare stimulation at intermediate spatial frequency under mesopic conditions, which could possibly be due to differences in spatial frequencies according to the devices used to conduct the CS test. While Chung et al [ 7 ] performed the CS test using the Optec 6 500 vision testing system based on spatial frequencies of 1.5, 3, 6, 12, and 18 cpd, our study was conducted under visual angles of 6.3°, 4°, 2.5°, 1.6°, 1°, and 0.64° (1.1, 1.8, 2.9, 4.5, 7.1, and 10.2 cpd, respectively). This difference may have introduced a lower spatial frequency bias in the test results, which is equal to larger visual angles in our study, and lowered the difference between CS caused by glare stimulation.…”
Section: Discussioncontrasting
confidence: 99%
“…Chung et al [ 7 ] compared the preoperative CS of 58 children with IXT with that of children at 3 months after strabismus surgery as well as with 34 normal controls. The children with IXT showed significantly lower CS at low and intermediate spatial frequencies under mesopic conditions, and at low spatial frequencies under photopic conditions compared with normal controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of nystagmus was similarly reduced at the end of the follow-up period, which was reported by the patient subjectively. We followed Chung's method to measure photophobia, using the CSV-1000 Contrast Sensitivity Chart under mesopic conditions with glare [4]. We encountered significant improvement in monocular contrast sensitivity from the 1st to the 52nd week, on lower spatial frequencies (three and six cycles per degree [c/d]).…”
Section: Case Reportmentioning
confidence: 99%